(untitled) (Global Journal of Management and Business Research, 2020)
Luxury is concept that has been viewed by different scholars and industry experts in the brand marketing evolutionary process. Many studies have found that a number of factors affect the purchase of luxury goods and many researchers have shown their interest in luxury consumption. Because of globalization, global luxury products have gained their presence in emerging nations such as Sri Lanka. Luxury consumption involves reflection of the social class, lifestyle and consumer#x2019;s personality backed by the prestige consumption mindset rooted in their financial power, individual values, social values and attitudes.